Cognitive Processing, PSTD Symptoms, and the Mediating Role of Posttraumatic Cognitions. [article]. - Nalipay, M. J.
The association between cognitive processing strategies and posttraumatic stress disorder (PTSD) symptoms has been demonstrated in a number of studies. However, the process of how cognitive processing determines PTSD symptoms is yet to be understood. The present study aims to clarify the relationship between cognitive processing and PTSD symptoms by examining the mediating role of posttraumatic cognitions in a sample of natural disaster survivors. The participants of the present study include 632 individuals who were directly affected by typhoon Haiyan. Findings of the study reveal that negative cognitions about the self mediated the relationship between cognitive processing of trauma (i.e., denial, regret, and resolution/acceptance), and PTSD symptom severity. Denial and regret were related to more severe PTSD symptoms through increased negative cognitions about the self. On the other hand, resolution/acceptance was associated with lesser PTSD symptom severity through decreased negative self-cognitions.